Analisis Faktor-faktor yang Memengaruhi Produksi Usahatani Bawang Merah di Desa Landangan Kecamatan Kapongan Kabupaten Situbondo - Untari, Wiwik Sri; Wijaya, Rifky Agnitian; Mufid, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Shallots have been one of the leading vegetable commodities grown by farmers for many years. In Landangan Village, the land area designated for shallots reaches around 6.8 hectares, with an average harvest of between 7 and 7.5 tons per hectare. Good market potential makes it a priority to continue development. This research aims to identify factors that influence shallot production in Landangan Village, Kapongan District, Situbondo Regency. Samples were taken by census, which means all members of the population were used as samples. The analytical method applied is Cobb-Douglas Function Analysis, which is used to determine production factors that influence shallot production. The test results using the statistical F test show that the variables of land area, seeds, fertilizer and labor have a significant influence on shallot production in Landangan Village. However, the t test results show that only the seed and fertilizer variables have a significant effect, while the land area and labor variables do not have a significant effect on shallot production in Landangan Village.